(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article reveals the problematic aspects of the interpretation of the definitions of “personal secrets” and “family secrets”. It is shown that personal and family secrets, as an object of civil legal protection, are a system of social relations that arises in relation to information that is confidential, the use and disclosure of which subsequently leads to a monetary recovery from the offender. The conclusion about the need to improve and further develop legislation in the field of the protection of the private life of citizens in social networks is formulated.